CRP Regulates D-Lactate Oxidation in Shewanella oneidensis MR-1 - Kasai, Takuya; Kouzuma, Atsushi; Watanabe, Kazuya (Frontiers in Microbiology, 2017)
Shewanella oneidensis MR-1 is a heterotrophic facultative anaerobe that respires using various organic and inorganic compounds. This organism has served as a model to study bacterial metabolic and regulatory systems that facilitate their survival in redox-stratified environments. The expression of many anaerobic respiratory genes in MR-1, including those for the reduction of fumarate, dimethyl sulfoxide, and metal oxides, is regulated by cyclic AMP receptor protein (CRP). However, relatively little is known about how this organism regulates the expression of catabolic enzymes catalyzing the oxidation of organic compounds, including lactate. Here, we investigated transcriptional mechanisms for the lldP (SO_1522) and dld (SO_1521) genes, which encode putative lactate permease and D-lactate dehydrogenase, respectively, and demonstrate that CRP regulates their expression in MR-1. We found that a crp-deletion mutant of MR-1 (∆crp) showed impaired growth on D-lactate. Complementary expression of dld in ∆crp restored the ability to grow on D-lactate, indicating that the deficient growth of ∆crp on D-lactate is attributable to decreased expression of dld. In vivo transcription and in vitro electrophoretic mobility shift assays reveal that CRP positively regulates the expression of the lldP and dld genes by directly binding to an upstream region of lldP. Taken together, these results indicate that CRP is a global transcriptional regulator that coordinately regulates the expression of catabolic and respiratory pathways in MR-1, including D-lactate dehydrogenase and anaerobic terminal reductases.